Pendidikan Islam Menurut Al-Ghozali (Telaah Atas Kitab Ihya’ Ulum Ad-dIN) - Muchasan, Ali (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2016)
Islam Education according to al-Ghazali in his book, Ihya ‘Ulum ad-Din, Islam education is a process of the human perfect achievement starts from the first of creation until the last of life as manifestation from the devotion to the God and his delegation on the earth that has a purpose to reach the happiness in the word and here after. Al-Ghazali thinking about Islam Education has two characteristic, sophistic and actuality usage. All activities of Islam Education should be pointed on the human perfect achievement in the word and here after.